A Simple and Sensitive High-Content Assay for the Characterization of Antiproliferative Therapeutic Antibodies - Stengl, Andreas (SLAS Discov, 2016)
Monoclonal antibodies (mAbs) have become a central class of therapeutic agents in particular as antiproliferative compounds. Their often complex modes of action require sensitive assays during early, functional characterization. Current cell-based proliferation assays often detect metabolites that are indicative of metabolic activity but do not directly account for cell proliferation. Measuring DNA replication by incorporation of base analogues such as 5-bromo-2′-deoxyuridine (BrdU) fills this analytical gap but was previously restricted to bulk effect characterization in enzyme-linked immunosorbent assay formats. Here, we describe a cell-based assay format for the characterization of antiproliferative mAbs regarding potency and mode of action in a single experiment. The assay makes use of single cell–based high-content-analysis (HCA) for the reliable quantification of replicating cells and DNA content via 5-ethynyl-2′-deoxyuridine (EdU) and 4′,6-diamidino-2-phenylindole (DAPI), respectively, as sensitive measures of antiproliferative mAb activity. We used trastuzumab, an antiproliferative therapeutic antibody interfering with HER2 cell surface receptor-mediated growth signal transduction, and HER2-overexpressing cell lines BT474 and SKBR3 to demonstrate up to 10-fold signal-to-background (S/B) ratios for treated versus untreated cells and a shift in cell cycle profiles indicating antibody-induced cell cycle arrest. The assay is simple, cost-effective, and sensitive, providing a cell-based format for preclinical characterization of therapeutic mAbs.